The instrumentality in the social worker’s daily word in the context of special social protection (Research, Society and Development, 2021)
This experience report aims to discuss the importance of instrumentality in the daily work of the Social Worker. Therefore, it became necessary to contextualize the theoretical dimension addressed by authors who dialogue on the topic, such as Yolanda Guerra, weaving threads with the researcher's work space as the central axis of discussion, presenting the home visit as a methodological instrument of highlighted work in the services performed at the Specialized Reference Center for Social Assistance – CREAS in Novo Oriente/CE. Nevertheless, the discussion takes into account the current context of the Covid-19 pandemic that the country is in, directly reflecting on the family, social and work routine. The methodology used consists of the bibliographic format and field research, with the intention of reflecting and explaining the different types of instruments and techniques that can be used to materialize the demands presented to the equipment, in particular, the home visit, object of study of this report, based on the theoretical contribution about the theme, which in professional practice become means for the objectification of intentions together with the subjects of their action.